Transforming Maternal and Child Health through Skilled Birth Attendance in Pastoral Ethiopia: Evidence from South Omo Zone - Mrs. Roman Tesfaye Abneh (My University, 2025)
This article presents empirical evidence on the impact of the Hailemariam & Roman Foundation (HRF)’s Reproductive, Maternal, Newborn, and Child Health (RMNCH) interventions implemented between 2021 and 2024 in the Hamar and Bena Tsemay districts of South Omo Zone, Ethiopia. The initiative achieved a 53.8% increase in skilled birth attendance in Hamar Woreda (from 34% to 52.3%) and an 8.6% increase in Bena Tsemay (from 86% to 94.6%), surpassing Ethiopia’s national target of 90% (FMoH, 2020). Over 140 health professionals, 20 health managers, and 23 community leaders were trained, while 64 Traditional Birth Attendants (TBAs) were integrated into the formal referral system —a strategy aligned with WHO recommendations for engaging informal providers to expand maternal health service coverage (WHO, 2015). Additionally, antenatal care (ANC) coverage increased, with over 80% of women attending at least one ANC visit, and 60% completing four or more—a significant improvement from baseline levels. Postnatal care (PNC) within 48 hours rose from under 20% to over 50%, and ambulance referrals quadrupled, enhancing emergency obstetric response. The findings demonstrate the effectiveness of combining health system strengthening, community-based engagement, strategic advocacy, and culturally tailored solutions to significantly improve maternal and neonatal health outcomes in underserved and remote regions, offering a compelling case for scaling up context-specific RMNCH strategies across pastoralist settings in sub-Saharan Africa.
Keywords: Maternal and Child Health; South Omo Zone; Ethiopia; Advocacy; Empirical Evidence; Hailemariam & Roman Foundation